2009
DOI: 10.1021/ac802406k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Microfluidic Device for the Electrochemical Determination of Halide Content in Ionic Liquids

Abstract: A microfluidic device designed for electrochemical studies on a microliter scale has been utilized for the examination of impurity levels in ionic liquids (ILs). Halide impurities are common following IL synthesis, and this study demonstrates the ability to quantify low concentrations of halide in a range of ILs to levels of ∼5 ppm, even in ILs not currently measurable using other methods such as ion chromatography. To validate the mixer device, the electrochemistry of ferrocene was also examined and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…Surface fouling of electrodes can occur in some circumstances. [5] To demonstrate that surface fouling was not occurring in the ionic liquid during repeated scanning over extended periods of time, the above experiment was repeated using a nonvolatile redox probe. The variation in ln(D) with 1/T is directly proportional to the activation energy of diffusion, E a , as expressed by Equation (4):…”
Section: Ferrocene Solutions Under a Flow Of Dry Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface fouling of electrodes can occur in some circumstances. [5] To demonstrate that surface fouling was not occurring in the ionic liquid during repeated scanning over extended periods of time, the above experiment was repeated using a nonvolatile redox probe. The variation in ln(D) with 1/T is directly proportional to the activation energy of diffusion, E a , as expressed by Equation (4):…”
Section: Ferrocene Solutions Under a Flow Of Dry Nmentioning
confidence: 99%
“…Ferrocene (Fc) has widespread applications, for example as an IUPAC recommended redox reference couple for non-aqueous electrochemical investigations, [1] as an electrochemical mediator, [2] reagent in organic synthesis [3] and probe (for viscosity changes, [4] mixing ability, [5] influence of electrode surface modification, [5] etc.). Fc sublimes relatively quickly at atmospheric temperature and pressure, [6,7] as well as in vacuo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the ease of electrode fabrication, on-line electrochemical detection has been widely used for continuous-flow microfluidic systems. [115][116][117][118] However, there are not many reports on its integration with EWOD devices. 119 In a study by Dubois et al, electrochemical detection was used as an orthogonal on-line technique to the off-line HPLC-UV absorbance (see Section 3.2.1) for the detection of final products of solution-phase synthesis.…”
Section: Electrochemical Detectionmentioning
confidence: 99%
“…Some techniques for characterizing the RTILs have already been developed on chip including solution phase synthesis 7 and halide content. 8 It has previously been shown that the quartz crystal microbalance ͑QCM͒ can be used to measure properties of RTILs, 9,10 which include the square root of the viscosity-density product ͑ ͱ ͒ using a small volume method requiring only 40 l. The viscosity of small volumes is often measured using cantilevers with a volume of only 1 ml. 11 The frequency response of a 5 MHz quartz crystal with a single sided liquid contact was characterized by the Kanazawa and Gordon equation ͑1͒, 12 which relates the change in frequency to the square root of the viscosity-density product,…”
Section: Introductionmentioning
confidence: 99%